Microplastic in the Digestive Tract of Kurau (Polydactylus octonemus) in the Coastal Waters of Karimun Besar Island, Riau Islands Province - Dalimunthe, Arif Munandar; Amin, Bintal; Nasution, Syafruddin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This study was conducted in March 2020 to know the presence of microplastics in the digestive tract of wild threadfin fish in the coastal waters of Karimun Besar Island, Riau Islands. The method used in this study was survey method. The results showed that the abundance of microplastics in the digestive tract of fish varies, the lowest of 2.89 particles / individu to the highest of 5.89 particles / individu with the dominant type found was fibre. The abundance of microplastic at station 1 was found to be higher than in station 2. The different anthropogenic activities in the two station were discussed. The Relationship between kurau fish size and microplastic abundance is weak with r = 0.21 and R² = 4.6% with the regression equation is y = 7.9747 – 0.0813x.